A Nonparametric, Distribution-Free Test for Serial Independence in Stock Returns - Ashley, Richard A.; Patterson, Douglas M. (Journal of Financial and Quantitative Analysis, 1986)
Richard A. Ashley, Douglas M. Patterson, A Nonparametric, Distribution-Free Test for Serial Independence in Stock Returns, The Journal of Financial and Quantitative Analysis, Vol. 21, No. 2 (Jun., 1986), pp. 221-227